FISHERY AND BIOLOGY OF PENAEID PRAWNS AT HARNAII, MAHARASHTRA - Deshmukh, V. D.; Hule, A. S.; Mane, S. J.; Sawant, M. S. (Journal of Indian Fisheries Association, 2015)
Penaeid prawn fishery at Harnaii in Ratnagiri District of Maharashtra was investigated during fishing seasons of 2002-03 and 2003-04 from mechanized (MLD) and hand operated trawlers (HT). During the two years, MLD contributed 86% and HT 14% to the average annual penaeid prawn catch of 2,242 t. The ’?atch showed two peaks, a major during October-December and a minor during April-May in both the gears but abundance of the individual species differed. P. stylifera, M. affinis, S. crassicornis, M. brevicornis, P. merguiensis and M. dobsoni mainly constituted the fishery and their species composition, seasonal abundance, annual size distribution and monthly mean size were investigated. Biological studies on food, size at maturity, spawning period, sex-ratio and juvenile abundance were carried out to Â·explain temporal abundance of the species in the fishery. Among the species P. stylifera, M. affinis and S. crassicornis exhibited distinct seasonality with two spawning peaks, one in pre-monsoon and the other in post monsoon period to produce two discrete broods while P. merguiensis despite two spawning peaks exhibited a single dominant brood. M. brevicornis showed monsoon and postmonsoon spawning while M. dobsoni showed only post-monsoon spawning. Migrations between nearshore and offshore waters resulted in mixing of the broods and they remained inseparable in the catch. Keywords: penaeid prawn fishery, biology, spawning seasons, recruit abundance.